‘But’ and its role in the building of mental representations - López-Astorga, Miguel (Praxis Filosófica, 2020)
The mental models theory rejects that sentences are linked to logical forms. From its perspective, their most relevant aspect refers to the semantic possibilities that correspond to them. In this way, the theory has analyzed in detail the real semantic role that the traditional connectives in logic can play in reasoning. However, given that logical forms are not important in its framework, in this paper, it is argued that those connectives are not the only operators that the mental models theory should review, and that there are other connectives present in most of the languages in general that can be interesting for it as well. That is the case of ‘but’ in English, which is addressed from the approach of the aforementioned theory here.